PROFESSIONAL IDENTITY COMPONENTS OF A DANCE TEACHER - Gorobeca, Paula (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The concept of professional identity is considered and topical from the perspective of different occupations. The professional identity of the dance teacher has so far not been researched scientifically and there are no studies about this concept. The article focuses on the term “teachers professional identity” and the formation process of the dance teacher’s professional identity model, as well as the explanation of components of this model from a dance teachers point of view. The aim of this article is to create a professional identity model of the dance teacher by analyzing scientific literature and using professional experience. The professional activity of the dance teacher directly affects the students both physically and psychologically, therefore it is especially important to pay attention to the issues of dance teacher’s professional identity, even more if these questions are not discussed in the study process and there are no related instructions or materials that reveal the essence of the professional identity concept in the world of dance. In a relatively short period of time that students spend in dance classes, teachers must maximize the positive impact on their students. Considering many factors of influence - family, school, friends, social networks, hobbies, dance educator should strive to create an understanding of behavior, aesthetics, tastes, positive relationships in the group, discipline and many more. Explaining professional identity from a creative point of view leads to greater insight into one's profession, as well as to assess the quality of one’s professional work and achievements.